Mitigating Human Error in Oil and Gas Accidents using TRACEr-OGI : A Middle Eastern Case Study - Onyekwere, Okwuchi Smith; Haruna, Amani; Azodo, Adinife (Risk Assessment and Management Decisions, 2024)
Persistent human error remains a significant contributor to accidents in the Middle Eastern oil and gas industry, despite ongoing efforts to analyze and mitigate these risks. This study investigates the applicability of the Technique for Retrospective and Predictive Analysis of Cognitive Error (TRACEr-OGI) for analyzing human error in offshore/onshore drilling accidents. Data from 16 accidents occurring between 2000 and 2014 were obtained from the IOGP safety zone and analyzed using TRACEr-OGI. A total of 1131 errors associated with the accidents were coded. The analysis revealed operator context (55.26%) as the most prevalent error source, followed by task errors (51.93%) within the context of incidence. This suggests a need for interventions targeting operator decision-making processes during drilling operations. Interestingly, both internal (33.66%) and external (33.17%) error modes were highly prevalent within the operator context. This indicates operators' susceptibility to errors arising from both internal cognitive factors and external influences on their decision-making. Additionally, the analysis identified personnel and management factors (23.41%) and psychological error modes (19.27%) as significant contributors to accidents. These findings suggest a multi-faceted approach is necessary to mitigate human error in Middle Eastern drilling operations. This study highlights the importance of considering not only operator cognitive factors but also broader personnel and management practices that can influence psychological well-being. By addressing these factors, the oil and gas industry can significantly enhance safety in drilling operations across the Middle East.